(untitled) (Economic and Political Thought, 2017)
Historically developed countries (USA, France, and UK) have not been developed on the basis of the principles of free trade, but protectionist policy. Still today, it is advisable that such a policy is good for developing countries. The necessity to protect a domestic market has been discussed for hundreds of years. Beside the main current of classical economics glorifying inter alia free trade, with the development of capitalism and schools of economic thought, alternative schools and currents indicating the need of protection came into being. Protectionist policy may adopt different forms, including tariff protection discussed in the article, especially the conception of infant industry, optimal duty as well as subsidies for producers, export promotion etc. Despite rather common criticism of tariff protection, it should be recognised that the assumptions described by F. List and A. Hamilton in the 19th century have solid theoretical foundations and many contemporary economists (e.g. P. Krugman) demonstrates the advantages of such policy. The author, with the use of theoretical models, assesses the influence of educational duty taking into consideration social welfare in a (small and big) country imposing tariffs as well as global welfare. He also uses statistical data concerning the United Kingdom, the USA, Japan and Germany in particular. The example of development, protection and dominance of steelmaking industry in the Nazi Germany is especially meaningful. The author uses econometric (cliometric) modeling to demonstrate the relationship between the rapid increase in steel production and the German government’s protectionist policy. The possibility of applying tariff protection in the contemporary economy, especially in case of developing countries, remains an important issue.